SYNTHESIS AND TAUTOMERISM OF 5,5-DISUBSTITUTED 1,2-OXATHIOLAN-4-ONE 2,2-DIOXIDES - Poliudov, A.O.; Havryshko, D.Y.; Dobrydnev, A.V.; Omelian Т.V.; Volovenko, Y.M. (Reports of the National Academy of Sciences of Ukraine, 2023)
Efficient and robust methods for the synthesis of 5,5-disubstituted 1,2-oxathiolan-4-one 2,2-dioxides, also known as β-keto-γ-sultones, including those with spatially strained spirocyclic substituents, have been developed. The influence of substituents in the 5th position of the β-keto γ-sultone framework on their ability to enolize and their reactivity was examined. The experimental data were fully supported by DFT calculations.